Implementing school programs supporting numeracy: What we can learn from a junior high school in Surakarta - Rofiah, Faizatur; Sujadi, Imam; Indriati, Diari (International Journal on Education Insight, 2024)
Mathematical literacy or numeracy has gained more attention in the education world in Indonesia. This can be seen through various efforts by the Ministry of Education to continually improve it. The research aims to provide an overview of the implementation of mathematics learning in junior high schools in Surakarta, resulting in the numeracy outcomes of students. This study adopts a qualitative approach with a case study strategy. The research data includes the implementation of numeracy, teacher activities, student activities, school environment, and documents. Data sources come from informants, including teachers and students. Data collection techniques involve interviews and documentation. The research findings reveal that the implementation of mathematics learning that strengthens numeracy at SMP Negeri 11 Surakarta and SMP Muhammadiyah Special Program Surakarta is in the stages of habituation and development. Mathematics teachers play roles as motivators, guides, and facilitators. Activities undertaken include providing books, familiarizing students with solving numeracy problems, assigning tasks, motivating students, organizing activities related to numeracy improvement, imparting knowledge, and allowing students to conduct studies.